Engineering, management and economics: a case study in alloying disparate elements. (9th February 2009) - Paxton, John
Although the Model T went out of production in 1927, its genesis and production had effects lasting long after the car. Its technical production evolution formed the basis for the first High-Volume Mass Production (HVMP) system in the world. This, in turn, engendered competition with General Motors, where the managerial advances by Alfred Sloan brought the modern corporation into being. These two advances, catalysed by the Model T, gave the USA a mature HVMP system, in place and producing, by 1935, when the rest of the world was still stuck in the craft-moving-to-mass-production transition era. The increased productivity that this gave the USA went far in helping to win World War II, forming today's nation and world. Not only the engineering, the management and the economics, but also an interactive mix of the three – and its emergent effects – was responsible.